2020
DOI: 10.21203/rs.3.rs-59456/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dysregulated Bile Acid Receptor-mediated Signaling and IL-17A Induction are Implicated in Diet-associated Hepatic Health and Cognitive Function

Abstract: Background: Chronic consumption of high sugar and high fat diet associated with liver inflammation and cognitive decline. This paper tests a hypothesis that the development and resolution of diet-induced nonalcoholic fatty liver disease (NAFLD) has an impact on neuroplasticity and cognition. Methods: C57BL/6 wild-type mice were fed with either a healthy control diet (CD) or a fructose, palmitate, and cholesterol (FPC)-enriched diet since weaning. When mice were 3-months old, FPC diet-fed mice were randomly as… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…For example, Dox administration can induce the decline of cognitive function (Jansen et al, 2008) and liver injury (Greupink et al, 2006). An experiment in a high-sugar and high-fat diet model showed that the abundance of Coriobacteriaceae involved in cholesterol metabolism was increased, and the altered gut microbiota and their metabolites resulted in systemic impacts on both hepatic metabolism and cognitive function (Jena et al, 2020). In our study, Coriobacteriaceae level was also found to be elevated in the Dox mice and positively correlated with clinical factors.…”
Section: Discussionsupporting
confidence: 60%
“…For example, Dox administration can induce the decline of cognitive function (Jansen et al, 2008) and liver injury (Greupink et al, 2006). An experiment in a high-sugar and high-fat diet model showed that the abundance of Coriobacteriaceae involved in cholesterol metabolism was increased, and the altered gut microbiota and their metabolites resulted in systemic impacts on both hepatic metabolism and cognitive function (Jena et al, 2020). In our study, Coriobacteriaceae level was also found to be elevated in the Dox mice and positively correlated with clinical factors.…”
Section: Discussionsupporting
confidence: 60%
“…The latest research shows that obeticholic acid (OCA), a derivative of BAs, reduced the expression of neuroinflammatory microglia and IL-1 in the hippocampus (Wu et al, 2021b). Several studies have suggested that BAs may play a role in cognitive dysfunction (Chen et al, 2020b;Jena et al, 2020). In summary, BAs may exert their effects on PD through anti-inflammatory and neuroimmunomodulatory mechanisms.…”
Section: The Roles Of Tryptophan Metabolites Basmentioning
confidence: 99%